2008
DOI: 10.1038/gene.2008.89
|View full text |Cite
|
Sign up to set email alerts
|

The shared CTLA4-ICOS risk locus in celiac disease, IgA deficiency and common variable immunodeficiency

Abstract: IgA deficiency (IgAD) and common variable immunodeficiency (CVID) often co-occur in families, associating with chronic inflammatory diseases such as celiac disease (CD). ICOS (inducible co-stimulator) and CTLA4 (cytotoxic T-lymphocyteassociated protein-4) may be important in both disorders, as ICOS is necessary for Ig class-switching and CTLA4 negatively regulates T-cell activation. Linkage and association of CD with CTLA4-ICOS is well documented, we thus aimed to further pinpoint CD susceptibility by haplotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 53 publications
(57 reference statements)
1
19
0
1
Order By: Relevance
“…A variety of studies found elevated levels of the soluble CTLA-4 protein in the plasma of patients with a variety of immunologically mediated diseases (Magistrelli et al, 1999). Polymorphisms in CTLA-4 have been associated with several autoimmune diseases including type 1 diabetes, inflammatory bowel disease, RA, celiac disease, multiple sclerosis, and systemic lupus erythematous (Haimila et al, 2009;Plant et al, 2010;Rai and Wakeland al., 2011). Two SNPs may influence the cell surface expression of the CTLA-4 molecule: -318C/T in the promoter region (rs5742909) and +49A/G in the first exon (rs231775).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies found elevated levels of the soluble CTLA-4 protein in the plasma of patients with a variety of immunologically mediated diseases (Magistrelli et al, 1999). Polymorphisms in CTLA-4 have been associated with several autoimmune diseases including type 1 diabetes, inflammatory bowel disease, RA, celiac disease, multiple sclerosis, and systemic lupus erythematous (Haimila et al, 2009;Plant et al, 2010;Rai and Wakeland al., 2011). Two SNPs may influence the cell surface expression of the CTLA-4 molecule: -318C/T in the promoter region (rs5742909) and +49A/G in the first exon (rs231775).…”
Section: Discussionmentioning
confidence: 99%
“…This region also contains the candidate CTLA4/ICOS genes, approximately 20 Mb apart, extensively studied in relation to CD due to their role in T-lymphocyte activity regulation, and recently associated with CD susceptibility in a population with proven linkage. 8 The PPP6C and PBX3 loci are located in 9q. This region showed linkage to CD in the North American population 9 but, in contrast to 2q33, no replication has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…The etiology of this disease is still unknown; several studies have shown the important association of certain HLA alleles with IgAD, although the specific location of the gene/s involved is controversial [3][4][5]. However, the HLA genetic component cannot explain the totality of the genetic influence on the disease, and very few additional genes have been associated with this immunodeficiency [6,7].…”
Section: Introductionmentioning
confidence: 99%